The Art of the Yellow Springs : Understanding Chinese Tombs. - Hung, Wu (Reaktion Books, 2011)
No other civilization in the pre-modern world was more obsessed with creating underground burial structures than the Chinese. For at least five thousand years, from the fourth millennium BCE to the early twentieth century, Chinese people devoted an extraordinary amount of wealth and labour to building tombs and furnishing them with exquisite objects and images. In art history these ancient burial sites have mainly been appreciated as 'treasure troves' of exciting and often previously unknown works of art. New trends in Chinese art history are challenging this way of studying funerary art: now a.